Penentu Tingkat Harga Umum dan Inflasi di Indonesia - Komaludin, Ade (Jurnal Trikonomika, 2009)
The objective of the research were (1) to know the fundamental factors of macroeconomic which determines general price levels and inflation rates during the period of the 2004-2008 and (2) to examine the stability of general prices and inflation models in Indonesia during the period of 2004-2008. Using the econometric approach (the time series analysis), the study found that general price levels in Indonesia during the period of 2004-2008 were determined by the fundamental factors of macroeconomic as follows: (a) price of import (b) nominal interest rates, (c) the global economic crisis of 2007-2008. All of those variables have positive relation with general price levels. The research was also found that inflation rates determines by the changes in nominal exchange rates in the one quarterly lag, price of import, money supply, nominal interest rates (SBI), and government expenditures. The research was also concluded that the long run equilibrium of general price model was happened. Employing the CUSUMSQ Test, the study provides evidence supporting that the model of general price levels was stable. Otherwise, the inflation model during the period of 2004-2008 was not unstable (there was change in parameters of the model).